Paclobutrazol induced physio-biochemical manifestations to ameliorate water deficit stress in rice (Oryza sativa) - GARG, NITIN KUMAR; MAHESHWARI, CHIRAG; CHANGAN, SUSHIL S; KUMAR, VAIBHAV; KUMAR, AMRESH; SINGH, ARCHANA; ALI, KISHWAR; TYAGI, ARUNA (The Indian Journal of Agricultural Sciences, 2019)
In this study, the mechanism of paclobutrazol (PBZ) mediated improvement in tolerance to water deficit in rice (Oryza sativa L.) genotypes were thoroughly investigated. Rice genotypes were subjected to different doses (0, 30, 60, 90, 120 ppm) of paclobutrazol. Study revealed that relative water content, membrane stability index, total chlorophyll and abscisic acid content significantly increased by application of PBZ in contrasting rice genotypes, i.e. Nagina-22 (drought-tolerant genotype), IR-64 (drought sensitive) and IR-64 DTY1.1 [drought-tolerant, near isogenic line of IR-64 developed by the introgression of a major QTL (qDTY1.1)] under polyethylene glycol mediated water deficit stress. The increase was found to be of higher magnitude in 90 ppm dose of paclobutrazol compared to other doses. Our results suggest that PBZ application could significantly improve tolerance in rice genotypes particularly susceptible genotype under limited water availability through selective changes in physio-biochemical parameters.